Public Satisfaction in Issuing Police Record Certificates Reviewed by the Quality of Service at the Sukoharjo Police - Widyasari Mahmudi; Siti Maryam; Ibnu Suryo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine and analyze the influence of service quality on public satisfaction in making SKCK at Sukoharjo Police. Service quality has 5 dimensions that are assessed, namely Tangibles (real evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (certainty), Empathy (empathy). The sampling technique used Convenience Sampling as stated by Malhotra is a non-probability sampling method where researchers choose the most easily accessible respondents and the number of samples is 75 respondents, namely public residents who are looking for SKCK at Sukoharjo Police. The instrument used is distributing questionnaires to respondents with a Likert scale. The results of the study show that all research variables including: tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4), empathy (X5) both simultaneously and partially have a positive effect on the variable of public satisfaction in making SKCK at Sukoharjo Police (Y). Keywords: service quality, community satisfaction in making SKCK